Preclinical Childhood Sarcoma Models: Drug Efficacy Biomarker Identification and Validation - Geier, Brian; Kurmashev, Dias; Kurmasheva, Raushan T.; Houghton, Peter J. (Frontiers in Oncology, 2015)
Over the past 35 years, cure rates for pediatric cancers have increased dramatically. However, it is clear that further dose intensification using cytotoxic agents or radiation therapy is not possible without enhancing morbidity and long-term effects. Consequently, novel, less genotoxic, agents are being sought to complement existing treatments. Here we discuss preclinical human tumor xenograft models of pediatric cancers that may be used practically to identify novel agents, and ‘omics’ approaches to identifying biomarkers that may identify sensitive and resistant tumors to these agents.